2018
DOI: 10.1038/s41398-018-0270-z
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β: a plausible mechanism of cognitive and hippocampal changes induced by erythropoietin treatment in mood disorders?

Abstract: Mood disorders are associated with significant psychosocial and occupational disability. It is estimated that major depressive disorder (MDD) will become the second leading cause of disability worldwide by 2020. Existing pharmacological and psychological treatments are limited for targeting cognitive dysfunctions in mood disorders. However, growing evidence from human and animal studies has shown that treatment with erythropoietin (EPO) can improve cognitive function. A recent study involving EPO-treated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 176 publications
(221 reference statements)
0
17
0
1
Order By: Relevance
“…Previous studies have identified that GSK-3β can phosphorylate various endogenous substrates, including proteins associated with metabolism and transcription factors. GSK-3β serves an important role in cell growth, development, tumorigenesis and the regulation of glucose homeostasis (99102). PI3K-dependent Akt is activated by insulin and growth factors that cause GSK-3β N terminal serine phosphorylation to inhibit GSK-3β activity.…”
Section: Pi3k/akt Signaling Pathway and Glycolysismentioning
confidence: 99%
“…Previous studies have identified that GSK-3β can phosphorylate various endogenous substrates, including proteins associated with metabolism and transcription factors. GSK-3β serves an important role in cell growth, development, tumorigenesis and the regulation of glucose homeostasis (99102). PI3K-dependent Akt is activated by insulin and growth factors that cause GSK-3β N terminal serine phosphorylation to inhibit GSK-3β activity.…”
Section: Pi3k/akt Signaling Pathway and Glycolysismentioning
confidence: 99%
“…Glycogen synthase kinase 3 beta (GSK3β) is an uncommon protein serine kinase that participates in several cellular signaling pathways and is associated with multiple rewards and motivational disorders (Xu et al, 2011 ; Shi et al, 2014 ; Huang et al, 2015 ; Patel and Woodgett, 2017 ; Inkster et al, 2018 ). The activity of GSK3β in the NAc core mediates the initiation and expression of methamphetamine-induced locomotor sensitization, suggesting that GSK3β may be a potential target for the treatment of psychostimulant addiction.…”
Section: Possible Influencing Factors That Mediate the Comorbidity Ofmentioning
confidence: 99%
“…Our experiments suggest that EPO could be a pro-inflammatory molecule since it triggers the expression of angiotensin I/II, which may act as an inflammatory agent by enhancing vascular permeability through VEGF. 39 , 103 106 Oxygen imbalance condition (1% O 2 ) increased EPO two-fold, whereas nine-fold for VEGF suggesting that EPO-induced angiogenesis signaling through VEGF is amplified under hypoxia. Our data demonstrated that EPO and VEGF expressions are regulated in parallel and they may communicate directly or indirectly through downstream regulators, including STAT3 and JAK2 phosphorylations.…”
Section: Discussionmentioning
confidence: 99%